2020
DOI: 10.1101/2020.08.29.273250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal and genomic analysis of additive genetic variance in breeding programmes

Abstract: This study demonstrates a framework for temporal and genomic analysis of additive genetic variance in a breeding programme. Traditionally we used specific experimental designs to estimate genetic variance for a specific group of individuals and a general pedigree-based model to estimate genetic variance for pedigree founders. However, with the pedigree-based model we can also analyse temporal changes in genetic variance by summarising sampled realisations of genetic values from a fitted model. Here we extend t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In fact, continued selection in Japanese Black population may have created LD across chromosomes (Bulmer, 1971). Based on the approach shown by Lehermeier et al (2017), Lara et al (2022) assessed the performance of partitioning the total additive genetic variance into genic variance, covariance due to intra‐chromosomal LD, and that due to inter‐chromosomal LD by using estimated marker effects, a different approach from ours. A more sophisticated way to cope with LD of two SNPs on different chromosomes might be to remove one SNP from the analysis: that is, removing the SNPs on the remaining chromosomes which are in LD with the SNPs on a particular chromosome in G 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, continued selection in Japanese Black population may have created LD across chromosomes (Bulmer, 1971). Based on the approach shown by Lehermeier et al (2017), Lara et al (2022) assessed the performance of partitioning the total additive genetic variance into genic variance, covariance due to intra‐chromosomal LD, and that due to inter‐chromosomal LD by using estimated marker effects, a different approach from ours. A more sophisticated way to cope with LD of two SNPs on different chromosomes might be to remove one SNP from the analysis: that is, removing the SNPs on the remaining chromosomes which are in LD with the SNPs on a particular chromosome in G 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In soybeans, the management of diversity is necessary to ensure useful variability for future breeding objectives, such as yield performance under drought or waterlogging (Valliyodan et al, 2017), the seed oil and protein content profiles (Stewart-Brown et al, 2019), and disease resistance (de Azevedo Peixoto et al, 2017). Monitoring genetic diversity in the genomic era can be performed through tracking overtime changes in allele frequencies (Allier et al, 2019b;de Castro Lara et al, 2020;Meuwissen et al, 2020). We showed that selection could quickly exhaust genetic diversity under closed breeding systems, and breeding systems can benefit from balancing short gains to preserve diversity and assure long-term gains.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic standard deviation was estimated as the standard deviation of the standardized genetic values. The genic standard deviation was estimated as the square root of the variance of genetic values assuming no linkage between the causal loci, directly obtained from AlphaSimR parental's population Lara et al, 2022;Pocrnic et al, 2023). All scripts for the implementation of the simulated scenarios and to plot and analyze the results can be found at: https://github.com/Resende-Lab/MaizeOCS-SimpleMating.…”
Section: Scenariosmentioning
confidence: 99%